Insulin Metabolism and Assessment of Hepatic Insulin Extraction During Liver Regeneration. A Study in a Rat Model. Issue 1 (2nd January 2020) - Kotsis, Thomas; Nastos, Constantinos; Stamatis, Konstantinos; Chondroudaki, Ioanna; Pafiti, Agathi; Frangou, Mata; Kotsovolou, Vina; Chondros, Konstantinos; Smirniotis, Vasileios; Fotopoulos, Alexios
ABSTRACT: Background : Liver regeneration is a complex procedure in which insulin metabolism has been implicated. The aim of this experimental study was to evaluate the role of insulin in rat hepatic regeneration following major hepatectomy (70%), employing an isolated perfused rat liver (IPRL) model to assess the extraction of insulin from the regenerating liver. Methods : Eighty-six male rats were randomized in 9 groups. A group of rats was studied at postoperative day (POD) 1 having a sham operation while control rats had no operation. All other animals were subjected to 70% hepatectomy. In phase B, at POD 1, 2, 3, 5, 7, and 14, the IPRL was applied. The regenerating liver was perfused with insulin (450 mu/ml) at a flow of 1.4 ml/gr liver/min for 20 min. Animal weight, liver weight, glucose, lactate, aspartate transferase (AST), alanine transferase (ALT), total bilirubin, albumin, prothrombin time (PT), insulin clearance, and tissue proliferating cell nuclear antigen (PCNA) expression were recorded. Results : We observed reduction of the liver's biochemical activities resulting in increase of AST (684%), ALT (532%), PT (27.7%), international normalized ratio (72%), and total bilirubin (82.8%) at first POD, while a normalization of the essential liver's functions occurs at fifth POD. Endogenous insulin concentration increased, while insulin extraction by the liver was reduced at the first POD in animals who underwent hepatectomy (13.94 ± 0.8 vs 7.97 ± 1.80 u/ml, p = 0.0005 and 71 ± 9.9 vs 165.88 µU/gr liver/min, respectively, p = 0.0005). Conclusions : Insulin seems to take part in hepatic regeneration, as the pancreas increases insulin production and the liver absorbs less despite the reduced hepatic mass and function.